2014
DOI: 10.1074/jbc.m113.544668
|View full text |Cite
|
Sign up to set email alerts
|

Rubredoxin-related Maturation Factor Guarantees Metal Cofactor Integrity during Aerobic Biosynthesis of Membrane-bound [NiFe] Hydrogenase

Abstract: Background: Biosynthesis of complex metal cofactors in [NiFe] hydrogenase is sensitive toward molecular oxygen. Results: A rubredoxin-like protein is required for hydrogenase maturation under aerobic conditions. Conclusion: The rubredoxin-like protein prevents oxidative damage of metallocenters, including the recently discovered [4Fe3S] center. Significance: Dedicated protection mechanisms enable biosynthesis of sophisticated metal centers in the presence of dioxygen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 65 publications
(103 reference statements)
0
7
0
Order By: Relevance
“…In this regard, other roles are also possible and compatible with the available evidence, for example as specific assembly factors and/or structural scaffolds for the hydrogenases. For example, it has been demonstrated that a rubredoxin-related protein is important for aerobic maturation of the group 1d [NiFe]-hydrogenase in R. eutropha (Fritsch et al, 2014). Furthermore, it is possible that other hypothetical proteins downstream of HucE and HhyE may also serve as electron acceptor candidates, in particular MSMEG_2717 that shares homology to PHG067, the proposed electron acceptor of R. eutropha (Schäfer et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, other roles are also possible and compatible with the available evidence, for example as specific assembly factors and/or structural scaffolds for the hydrogenases. For example, it has been demonstrated that a rubredoxin-related protein is important for aerobic maturation of the group 1d [NiFe]-hydrogenase in R. eutropha (Fritsch et al, 2014). Furthermore, it is possible that other hypothetical proteins downstream of HucE and HhyE may also serve as electron acceptor candidates, in particular MSMEG_2717 that shares homology to PHG067, the proposed electron acceptor of R. eutropha (Schäfer et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Recruitment of auxiliary proteins is not uncommon in the biogenesis of unique Fe/S proteins. An example of such an auxiliary component is the rubredoxin-related HoxR protein, which prevents oxidative damage to metallocenters during their biogenesis in the [NiFe] hydrogenase of Ralstonia eutropha H16 (38). In this context, NqrM may represent an additional, Na ϩ -NQR-specific protein that directly functions in Na ϩ -NQR maturation in the respective bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Rx. gelatinosus CBS contains HupI (HoxR homolog in R. eutropha H16), a rubredoxin-type FeS protein deemed essential in assembling the O 2 -tolerant MBH in R. eutropha H16 when cultured in aerobic environment [54] , [56] . Future studies may reveal whether the supernumerary cysteines contribute to the O 2 -tolerance of the MBH in Rx.…”
Section: Resultsmentioning
confidence: 99%